Edible insect as an alternative protein source: a review on the chemistry and functionalities of proteins under different processing methods. Issue 4 (April 2023) - Queiroz, Lucas Sales; Nogueira Silva, Naaman Francisco; Jessen, Flemming; Mohammadifar, Mohammad Amin; Stephani, Rodrigo; Fernandes de Carvalho, Antonio; Perrone, Ítalo Tuler; Casanova, Federico
Abstract: The consumption of edible insects can be anadvantageous alternative to the conventional food supply chain, which involves global water waste, land deficit, undernutrition, and starvation. Besides the nutritional aspects, insect proteins have demonstrated a wide range of functional properties such as foamability, emulsifying and gelling abilities. The protein content and amino acid profile of some insects have revealed a good nutritional value and interesting functional properties. However, it is crucial to comprehend how the protein quality is affected by insect feeding, drying, and defatting. There is a knowledge gap about the impact of industrial treatment, such as pH, ionic strength, and heat treatment, on insect proteins' functional properties. In this review, we have aimed to highlight the potential application of insect proteins as a nutritional source and their promising technological applications. The study reported the principal insect protein characterization methodologies that have been investigated in the literature aiming to correlate the physicochemical parameters to possible protein functionalities. The research on the functional properties of insect proteins is at the exploratory level. Further detailed studies are needed to clarify the structure-function relation of insect proteins and how these functionalities and insect processing can increase consumer acceptance. Graphical abstract: Image 1 Highlights: SC-CO2 and HHP are promising defatting methods compared to solvent extraction. Insect protein extracts showed greater WHC/OHC than insect flour. Insect proteins show promising gelling capacity and strength at neutral and alkaline pH. There is an improvement in colloidal properties when protein extract is used instead of flour.